2021
DOI: 10.3389/fendo.2021.745395
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy Rate of Bethesda Class III Thyroid Nodules Based on the Presence of Chronic Lymphocytic Thyroiditis in Surgical Patients

Abstract: BackgroundHashimoto’s thyroiditis (HT), also known as chronic lymphocytic thyroiditis (CLT), may interfere with the accurate cytological diagnosis of thyroid nodules. Recently, HT has been considered a premalignant condition for thyroid cancer development. The diagnosis of atypia of undetermined significance/follicular lesions of undetermined significance (AUS/FLUS) thyroid nodules is challenging and evidence for the malignancy risk of AUS/FLUS thyroid nodules coexisting with CLT is scarce. Therefore, we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…A similar finding was also confirmed by Cho et al. ( 21 ), Erdogan-Durmus et al. ( 2 ), and in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…A similar finding was also confirmed by Cho et al. ( 21 ), Erdogan-Durmus et al. ( 2 ), and in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the ultrasonographic signs that seem most associated with “critical” reassessment at a second ultrasonography, and most associated with carcinoma risk, were spiculated or microlobulated margins and microcalcifications. These findings correlate well with those of other studies, in which microcalcifications, nodule shape, margin irregularity, and hypoechogenicity were found to be variously correlated with increased risk of malignancy [ 12 , 27 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…Their authors indicated that HT was not a risk factor for thyroid malignancy nodules with category III. Cho et al [38] found the same frequency of malignancy-48%-in patients with and without HT. Rotondi et al [39] also reported similar values-11.0% vs. 13.4%, respectively.…”
Section: Discussionmentioning
confidence: 80%